The Influence of Chinese Online Novels on the Values of Adolescents - Assel P. Bissenbayeva; Cheng J. Cheng; Nurhalyk Abdurakyn; Nurzhan B. Saparbayeva; Gulshat J. Serikbayeva (National Research Mordova State University, 2024)
Introduction. With the development of the Internet, the popularity of online novels, especially in China, prompts the declining interest in reading paper books. The potential impact of online novels on adolescents has become a matter of public concern. Most studies examine the role of online novels in students' learning process, as well as the impact on young people's communication and social interaction. However, so far, the impact of online novels on adolescents' values and psychology has been understudied despite their critical importance in shaping young peopleʼs identity. Therefore, the purpose of this study is to determine the influence of online novels on the values and psychology of Chinese secondary school learners. Materials and Methods. To address this challenge, a survey was conducted among students attending Yifu Educational Institution in Nanning, China. Questionnaires developed through the Question Star app were distributed through relevant user groups on social media platforms including WeChat and Tencent QQ. Results. As a result, positive (increased general knowledge and literacy, the opportunity to spend free time productively) and negative (impact on learning and physical health, decreased literary abilities, promotion of tendencies harmful for society) characteristics of the influence of online novels on adolescents were identified. Practical recommendations were formulated aimed at counteracting negative impact of online novels on adolescents such as the need to strengthen the ideological and moral education of students, the necessity to develop national cultural superiority and pride of modern youth, as well as to introduce young people to useful bibliography. Discussion and Conclusion. The results obtained will make a significant contribution to such fields as psychology, sociology and education. Also, the results of the study will serve as a basis for the development of new approaches to combat the negative impact of Internet novels on the values of adolescents. The results of the study may be useful for specialists of educational institutions and all those who care about the upbringing of the younger generation.